Experiences of Navigator, a Finnish patient-segmentation service, in primary care: A mixed-methods study - Riikka Riihimies; Elise Kosunen; Tuomas Koskela (Finnish Social and Health Informatics Association, 2021)
Aging and multimorbid populations burden health services worldwide. Segmenting patients with similar health service needs into different groups and guiding care providers to tailor services to these groups could reduce this burden. Methods of patient segmentation have been based on, e.g., databases. However, the Finnish patient-segmentation innovation Navigator (Suuntima) considers patients' perspectives on their coping in everyday life, as well as professionals' views of the patients' state of health. The segmentation is based on questions. The resulting care pathway related to the group helps professionals to coordinate patients' health care and patients to utilize appropriate services. This first part of Navigator's validation study evaluates its feasibility and content and face validity. We assess the web-service's user experiences at nurses' appointments with diabetic patients, time consumption, and Navigator's question relevance, comprehensiveness, and comprehensibility. This mixed-methods study uses user experience questionnaires for both patients and professionals, and semi-structured focus-group interviews for professionals. We used descriptive statistics in the quantitative data analysis of the questionnaire study and thematic analysis to identify the codes and themes in the interview data. All 304 Navigator queries were completed at appointments. Most patients found Navigator easy to use. It helped in considering their situation better and from new perspectives. Most patients did not find it too time-consuming. Most professionals found it easy to use and suitable for appointments and patient segmentation. The questions were easy and unambiguous, and they assisted in discussing new or sensitive issues. Most queries were completed in less than 19 mins and less time was used if the patient was assigned to the nurse. Thematic analysis raised five main themes: 1) Well-functioning web-service, 2) Stimulus for conversation and action, 3) Rationale to complete Navigator with a professional, 4) Training and experience ease the use of Navigator, and 5) Navigator's room for improvement. Subthemes were identified for three main themes. We consider Navigator's feasibility and face validity to be favorable. We suggest user instructions and the clarification of concepts to support the questions' comprehensibility. Some patients may benefit from a nurse's presence when responding to Navigator's questions.